1992
DOI: 10.1016/0009-2509(92)80309-z
|View full text |Cite
|
Sign up to set email alerts
|

A numerical model of gas-fluidized beds

Abstract: A first-principles model for a gas-fluid&d bed based on the so-called "two-fluid model" (TFM) has been developed_ In the TFM approach, both phases are considered to be continuous and fully interpenetrating. The equations for mass, momentum and thermal energy conservation, supplemented with the necessary constitutive equations, have been sotved by a finite-difference technique on a mini-computer. The computer model calculates the porosity, the pressure, the fluid phase temperature, the solid phase temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
138
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(157 citation statements)
references
References 21 publications
1
138
0
3
Order By: Relevance
“…17,18 To account for particle−particle interactions, the kinetic theory of granular flow 19,20 (KTGF) is used. In this work, the standard TFM equations were used to describe the continuum modeling approach for the gas and solids phases.…”
Section: ■ Two-fluid Modelmentioning
confidence: 99%
“…17,18 To account for particle−particle interactions, the kinetic theory of granular flow 19,20 (KTGF) is used. In this work, the standard TFM equations were used to describe the continuum modeling approach for the gas and solids phases.…”
Section: ■ Two-fluid Modelmentioning
confidence: 99%
“…Measured gas and particle mean velocities in a bubbling bed using the robust technique developed in the previous quarter 4  Analyzed velocity profiles by checking for self-similar behavior  Validated the gas-solid equations in MFIX with experimental data from a bubble injection experiment performed by Kuipers (1990). 5  Measured mean velocity profiles by varying the fluidized state of the emulsion using the LDV technique.…”
Section: Quartermentioning
confidence: 99%
“…Additional validations of the gas-solid equations used by MFIX were made by comparisons with the experimental data of Tsuji et al (1983) for vertical risers and Kuipers (1990) for bubble injection, and were found to match favorably. These are, however, not included in this report.…”
mentioning
confidence: 99%
“…For the past two decades, particulate flows have been an active area of research and two widely used approaches are now considered state of the art. The first approach is based on an Eulerian continuum model of two phase flows, which only describes the averaged behaviour of the multi-phase media [1]. The second approach is based on an Eulerian-Lagrangian approach using finite-volume/finite-difference methods on a fixed grid as a fluid solver and either an immersed boundary [2], fictitious domain (FD) [3], marker and cell [4] or discrete-element method (DEM) [5] for the particles.…”
Section: Introductionmentioning
confidence: 99%